Hubungan antara Penguasaan Kosakata dengan Kemampuan Story Telling pada Anak Autism Spectrum Disorder di PLDPI Kota Surakarta - Anggita Maharani, Dian; Sudarman, Sudarman (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: The vocabulary allow a person to speak well and correctly, one of which is the ability to tell or can also be called by story telling. The problem of the language is close to the child special needs. One of them is a language problem that occurs in children with autism spectrum disorder. However, children who have autism spectrum disorder have different characteristics of language disorders. Purpose: This research aims to know if there is a relationship between the ruler of the vocabulary with the story telling ability in the autism spectrum disorder in PLDPI Surakarta city. Method: This type of research is a quantitative research with observative analytical research design and cross sectional design. The quantity of samples in this research is 30 autism children in PLDPI Surakarta city using Purposive Sampling technique. The statistical tests used are Spearman-rank. Research Result: The analysis results show the value of p is 0.632 that means p > 0.005, and the significance value is 0.000 it means sig. (2-tailed) < 0.05. It can be concluded that there is a relationship between the rulers of the vocabulary with the story telling ability in autism spectrum disorder. Conclusion: Vocabulary has a close relationship with children's storytelling abilities, because to be able to tell stories children must first master vocabulary. When the child understands the vocabulary, the child is able to form phrases, these phrases will develop again into sentences and the series of sentences will eventually form a story. Keywords: Vocabulary, Story Telling, Autism Spectrum Disorder